The snoRNA MBII-52 Regulates Cocaine-Induced Conditioned Place Preference and Locomotion in Mice - Chen, Hongjie (Public Library of Science, 2014)
Cocaine dependence involves in the brain's reward circuit as well as nucleus accumbens (NAc), a key region of the mesolimbic dopamine pathway. Many studies have documented altered expression of genes and identified transcription factor networks and epigenetic processes that are fundamental to cocaine addiction. However, all these investigations have focused on mRNA and/or miRNA, which may not reflect the involvement of small nucleolar RNAs (snoRNAs), which has been implied in a broad range of biological processes and complex diseases including brain development and neuropathologocal process. To further address the role of snoRNA in cocaine addiction, we show that repeated exposure and conditioned place preference (CPP) training to cocaine negatively regulates the expression of MBII-52 mRNA level, which is a brain-specific C/D box snoRNA, but not influences the serotonin receptor 2C (5HT2CR) mRNA level in NAc. Furthemore, we show, developing lentiviral vector (LV)-expressing MBII-52 and LV-5HT2CR for stable and regulatable MBII-52 and LV-5HT2CR expression. LV-MBII-52 and LV-5HT2CR expression in NAc attenuate cocaine induced CPP and locomotor activity. Taken together, these findings show that MBII-52 and 5HT2CR exert an inhibitory influence on the behavioral responses to cocaine exposure.